Standardization of Seed Germination in Fever Nut (Guilandina bonduc L.) for Adaptation in Western Himalayas as its New Abode - Patade, Vikas Yadav; Kumar, Kundan; Gupta, Anand Kumar; Grover, Atul; Negi, Prem Singh; Dwivedi, Sanjai Kumar (Indian Forester, 2020)
Fever nut (Guilandina bonduc L.) a fast growing important medicinal plant of Fabeaceae family is widely distributed throughout the plains near seacoasts and other Southern regions of India. However, information is not available regarding its adaptation in Western Himalayas, which is known for its wealth of medicinal herbs. The study indicates that the plant is amenable to successful adaptation in Western Himalayas. Further, due to uncontrolled exploitation for traditional medicines from nature, the plant has become endangered. The simple and effective method for its large scale propagation through seed germination are reported in the study. The method involves pre-treatment of seeds with concentrated sulphuric acid for 90 min in fresh or one year stored seeds. The results of the present study may be useful in large scale propagation of the plant in its new abode in Western Himalayas for further utilization in different types of herbal medicines and other purposes.